The right to choose or having no choice: Retirement or employment. Dilemmas related to old age (remarks based on Polish legal regulations) - Tatiana Wrocławska (Economic and Environmental Studies (E&ES), 2017)
In the title of this work, one may notice a nod towards Shakespearean drama. Here the tragedy of the situation relates to making a choice on whether people at the age of retirement should be left with an unequivocal choice: either work and receive remuneration for it, or retire. However, would it not also be justified to undertake such activities which support pensioners in work and thus create an opportunity for people who receive a retirement pension to work as long as possible? The discussion on this matter is significant, as the lowering of the retirement age is happening in Poland. Postponement of retirement and continuing in work after reaching retirement age may significantly increase retirement income. Therefore, this is decisive when making decisions about whether to take retirement or continue in employment. The legal regulations may considerably affect this process. Hence, the discussion about the adequacy of the legal instruments which allow a choice to be made is particularly important and topical. The presented analyses allowed this author to provide some assessments with relation to the ongoing issue of the lowering of the retirement age, determined - as politicians claim - to give people a choice. The presented topic fits into the framework of making work sustainable over a lifetime, which is a key facet of the promotion of longer and healthier working lives, as it is inextricably linked with the well-being of society.
Keywords: J21; J26; J48; J70; K31; 330; retirement pension; old age; retirement age; termination; flexible employment